Drought legacies are short, prevail in dry conifer forests and depend on growth variability. (23rd June 2020) - Gazol, Antonio; Camarero, Jesús Julio; Sánchez‐Salguero, Raul; Vicente‐Serrano, Sergio M.; Serra‐Maluquer, Xavier; Gutiérrez, Emilia; de Luis, Martín; Sangüesa‐Barreda, Gabriel; Novak, Klemen; Rozas, Vicente; Tíscar, Pedro A.; Linares, Juan C.; et al.
Abstract: The negative impacts of drought on forest growth and productivity last for several years generating legacies, although the factors that determine why such legacies vary across sites and tree species remain unclear. We used an extensive network of tree‐ring width (RWI, ring‐width index) records of 16 tree species from 567 forests, and high‐resolution climate and normalized difference vegetation index (NDVI) datasets across Spain during the common period 1982‒2008 to test the hypothesis that climate conditions and growth features modulate legacy effects of drought on forests. Legacy effects of drought were calculated as the differences between detrended‐only RWI and NDVI series (i.e. after removing long‐term growth trends) and pre‐whitened RWI and NDVI series predicted by a model including drought intensity. Superposed Epoch Analysis (SEA) was used to estimate whether legacy effects differed from random. Finally, legacy effects were related to water balance, growth persistence and variability, and tree species identity. We found a widespread occurrence of drought legacy effects on both RWI and NDVI, but they were seldom significant. According to SEA, first‐year drought legacies were negative and different from random in 9% and 5% of the RWI and NDVI series respectively. The number of significant second‐ and third‐year legacies was substantially lower. Differences between RWI and NDVI legacies indicate that canopy greenness and radial growth responses to drought are decoupled. We found variations in legacies between tree species with gymnosperms presenting larger first‐year drought legacies than angiosperms, which were exposed to less severe droughts. Greater growth variability can explain the presence of first‐year RWI legacies in gymnosperms from dry sites despite that the relationship between growth variability and legacies was complex. Synthesis . Accounting for species and site responses to drought provides a better understanding of the magnitude and duration of drought legacies on forest growth and productivity. Despite the widespread occurrence of growth reductions in the years during and after drought occurrence, significant legacies were not very common, mostly lasted one year, and were more widespread in gymnosperms. These are relevant factors to be considered in the future when studying the consequences of drought on forest productivity and tree growth. Abstract : Legacy effects of drought on tree growth (RWI, ring‐width indices) and forest productivity (NDVI) vary between tree species. Drought legacies are more common for gymnosperms than for angiosperms and usually last for one year. Growth variability partially explains the variation in drought legacies between species despite the fact that this relationship is complex and species‐specific.